TEST 123 - Musa, Mohamad Ridzuan Musa; Azhar, Anis Aziyah (SPU Publisher, 2025)
The International Islamic University Malaysia's repository system, IRep commenced operation in June/ July 2011. This is a digital repository of published publications and scholarly output of IIUM staff encompassing various subjects and disciplines. The publications include articles, books, book chapters, proceeding papers and monographs.